HUBUNGAN PENGETAHUAN DENGAN PENCEGAHAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - siswandi, iyar; Ikshan, Ikshan (JURNAL KESEHATAN KARTIKA, 2025)
Background: Diabetes Mellitus is one of the endocrine system disorders that frequently occurs in society, with an annual increase of 56% in sufferers due to the instability of carbohydrates, fats, and proteins, leading to elevated blood glucose levels. This occurrence is influenced by the community's level of knowledge, which is lacking in understanding diabetes mellitus prevention methods. Objective : The purpose of this study is to determine the relationship between knowledge and the prevention of blood glucose levels in patients with type 2 diabetes mellitus. The sample used in this study consists of 55 respondents. This method utilizes a Cross-Sectional approach. Bivariate data analysis resulted in findings using the Chi-square test. Regarding the independent and dependent variables, a P-Value of 0.016 (<0.05) was obtained. Result of the OR = 0.241. Suggestions for future researchers can include prevention measures that may influence the increase in blood glucose levels. In conclusion, there is a significant relationship between knowledge and the prevention Hyperglycemia in type 2 diabetes mellitus patients